Finklebine, Sources Of The African-American Past - Primary Sources In American History; Thomas, Ed., Plessy C. Ferguson - A Bried History With Documents - Peters, T. Ralph (Teaching History: A Journal of Methods, 1998)
Two new works document the history of African-American struggle for equal rights in the nineteenth and twentieth centuries. Finklebine’s work, Sources of the African-American Past: Primary Sources in American History, is a welcome addition to the primary source literature on the perpuity of, and challenges to, the social positions African Americans inhabited from the slave trade through recent times. Organized chronologically along topical lines, the book covers the slave trade, the colonial experience, the Revolution, free blacks, slavery, black abolitionism, emancipation, Reconstruction, segregation, progressivism, the New Deal, the two World Wars, migration, school segregation, the civil rights movement, black nationalism, and African Americans since 1968.